PENGARUH RASIO LIKUIDITAS DAN RASIO SOLVABILITAS TERHADAP RASIO PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK JAKARTA - Gultom, Fratis F. (UNIKA Santo Thomas, 2010)
Calculation of financial ratios is one of the financial statement analysis tools to compare the data with other data, to determine the interrelationships between assets, liabilities and capital which can then be determined level of liquidity, solvency and profitabilitas.Berdasarkan preliminary research note that the ratio - financial ratios ( liquidity ratio and solvency ratio) of manufacturing companies that have gone public on the Jakarta Stock Exchange has a different relationship when associated with profitabiitas. Based on the description, research the problem can be formulated as follows: